THE IMPLEMENTATION OF SCIENTIFIC APPROACH ON ENGLISH LANGUAGE LEARNING OUTCOMES IN THE CONTEXT OF CURRICULUM 2013 AT SMK PGRI ENREKANG - Fauziah M, Era; Ilmiah; Junaid (English Language Teaching Methodology, 2025)
The application of a scientific approach in learning English is a teaching method that focuses on the scientific process, which aims to improve students' understanding and skills in English. This research aims to find out how teachers apply a scientific approach in learning English and how students respond to implementing this approach. It is hoped that this research can contribute to the development of more effective English learning methods, while increasing students' self-confidence in learning. The research subjects were two English teachers at SMK PGRI Enrekang who had been interviewed and observed, as well as eight class XII students who were selected as representatives through a random sampling method. Data collection was carried out through interviews and direct observation to obtain in-depth information regarding the learning process based on a scientific approach. The research results show that the application of a scientific approach in English language learning based on the 2013 Curriculum is able to improve students' critical, creative and analytical thinking skills. Through the stages of observing, asking, experimenting, associating, and communicating, students not only learn passively, but also actively apply and develop their language skills in real situations. Although there are challenges in terms of time allocation and student readiness, this approach has a significant positive impact on the quality of English learning in the classroom. Overall, the scientific approach is an effective strategy in improving students' English language skills, as well as supporting the achievement of the 2013 Curriculum objectives of creating relevant, structured and meaningful learning.